Pengaruh penggunaan media sosial TikTok terhadap kreativitas mahasiswa: Studi kasus mahasiswa di Kota Malang - Ramadani, Naina Alfiah (Maliki Interdisciplinary Journal, 2024)
In this modern era, technology is developing day by day and getting faster in all areas of life. Also with the development of social, almost everyone has a social media account. TikTok is currently one of the most famous social media, not only in our country Indonesia but even the whole world uses TikTok. Tiktok is a social media for sharing very different videos, which allows users to do many things, including in the business field. Nowadays, TikTok users are spread across all circles and one of them is students, most students use the TikTok application. Currently, the average student has very high creative content writing skills in order to build an audience that can support them through the creativity of the content they create. This application has many benefits and also positive impacts that can be shared, such as various tips, using it as product advertising and sharing educational videos. This research uses empirical research. Empirical research places the study of social phenomena. Therefore, this problem is always associated with social problems.